Maya potters' indigenous knowledge: cognition, engagement, and practice - Arnold, Dean E., author; University Press of Colorado, publisher (Colorado State University. Libraries, 2018)
Based on fieldwork and reflection over a period of fifty years, Arnold utilizes engagement theory to describe the indigenous knowledge of traditional Maya potters in Ticul, Yucatán, Mexico. Arnold examines craftspeople's knowledge and skills, their engagement with natural and social environments, the raw materials, and their process.--Provided by publisher.
Introduction -- How was the data collected? -- The potters' engagement with the perceived landscape -- The potters' engagement with raw materials -- The potters' engagement with paste preparation -- The potters' engagement with vessel forming -- The potters' engagement with drying and firing -- Ticul Pottery as a "distilled landscape"/"taskscape" -- Conclusion.
Keywords: Maya pottery -- Mexico -- Ticul; Mayas -- Material culture -- Mexico -- Ticul; Cognition and culture; Potters -- Mexico -- Ticul